Financial Analysis of Purple Sweet Potato Flour Production Business - Marselus Hendro; Sethyo Vieni Sari; Ahmad Mustangin (International Research & Development for Human Beings (IRDH), 2024)
Purple sweet potato flour can be used as a substitute for wheat flour in donuts, bread, brownies, noodles, cookies, muffins, and other products. Processing purple sweet potato into flour can not only extend its shelf life but also make it easier to process into a variety of food products. With its nutritional content, such as minerals, vitamins, crude fiber, anthocyanin compounds, and antioxidants, sweet potato is very suitable for staple food development. Although purple sweet potato has a lot of potential, commercially it has not been widely used as a raw material for salak seed kolak. One of the problems encountered is the lack of in-depth economic analyses on the manufacture of purple sweet potato flour and its use as a raw material for salak seed kolak. The purpose of this study was to determine the business feasibility of making purple sweet potato flour, variations in drying temperature, and the best drying method, as well as the level of panelist acceptance (sensory test) of sweet potato flour and its application to the resulting salak seed kolak. The research used an experimental design with variations in drying methods and temperatures, namely cabinet dryer with a temperature of 70 OC) and direct sun drying. The results of this study indicate that the business of making sweet potato flour can be declared feasible, seen from the R / C ratio value greater than 1, namely 1.1, and the payback period of 3.6, which is a long time to be able to return investment capital.